PERSEPSI MASYARAKAT DALAM PARTISIPASI POLITIK : Studi Kasus: Pemilihan Kepala Daerah Tahun 2019 di Desa Masuru Kecamatan Kwandang Kabupaten Gorontalo Utara - Pilomonu, Sri Nande; Rachman, Ellys; Talalu, Mohamad Abubakar (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
This research aims to determine Community Perceptions in Political Participation (Case Study; 2019 Regional Head Election in Masuru Village, Kwandang District, North Gorontalo Regency). This research consists of three focuses, namely knowledge, community expectations and evaluation. The research method used is descriptive qualitative. The results of the research concluded that public knowledge in political activities is still low, this can be seen from the apathy of the public in the 2019 Gorontalo Regency Regional Head election. The public's expectations regarding the benefits of every political activity are quite low, this can be seen from the disappointment of some in the community. The public's assessment of the impact of participation in political activities tends to be negative, with many people feeling reluctant to deal with politics.